INDUCTION OF HEPATIC GLUTATHIONE-S-TRANSFERASE ACTIVITY BY Orthosiphon stamineus, BENTH IN STZ-INDUCED DIABETIC RATS - J.H. CHIN; S. ISMAIL; A.H. HUSSIN (Universiti Sains Malaysia, 2008)
The aim of this study was to investigate the acute (one-day treatment) effect of a methanol extract of Orthosiphon stamineus, Benth on glutathione-S-transferase (GST) activity in streptozotocin (STZ)-induced diabetic young male and female Sprague Dawley (SD) rats. The methanol extract of O. stamineus was administered orally (5, 31.25, 125 and 500 mg/kg) to diabetic rats, and the effect on GST activity was measured by the method of Habig et al. (1974). No lethality and no significant changes in body weight and water intake were observed in the treated group as compared to the control group. A significant increase in the activity of GST was observed in the liver S-9 cytosolic fraction of diabetic male SD rats treated with 125 mg/kg (P < 0.01) and 500 mg/kg (P < 0.01) of the methanol extract O. stamineus. Administration of 500 mg/kg (P < 0.01) of the methanol extract of O. stamineus to diabetic female SD rats increased GST activity when compared to the control group. This study indicates that the methanol extract of O. stamineus could affect the activity of GST in rat liver and the effect seen was dose-dependent